Testing the Role of Ethnicity and Health Consciousness in Preventive Health Behaviors - 최윤형; 권경난 (Journal of Multicultural Society : OMNES, 2020)
As preventive health care has gained in importance, health researchers have paid increasing attention to the role of health consciousness in preventive health behaviors. However, little is known about how ethnicity comes into play in the relationship between health consciousness and preventive health behaviors. The purpose of the current study is, thus, twofold. First, we attempt to test whether health consciousness actually predicts preventive health behaviors such as healthy eating, regular exercise, doctor visits, alternative medicine use, and information seeking; second, we explore the main effect of ethnicity (African vs. Caucasian Americans) on preventive health behaviors and its moderating effect on the relationship of health consciousness and preventive health behaviors. Analyzing the Life Style survey data collected by DDB Needham Co., an international marketing communication firm, we found that health conscious individuals would be more likely to practice preventive health behaviors such as healthy eating, regular exercise, alternative medicine use, and information seeking. Some differences emerged between the two ethnic groups in healthy eating, regular exercise, and doctor visits. We also found a marginally significant interaction effect of ethnicity by health consciousness on healthy eating, such that when the level of health consciousness was low, African Americans showed healthier eating than Caucasian Americans. These differences underscore the need to develop culturally appropriate, evidence-based health promotion messages to maximize preventive health behaviors when targeting different ethnic groups.
Keywords: ethnicity; health consciousness; preventive health behavior; healthy lifestyle; health information seeking